Quality control in GNSS reflectometry method for tide observations - Agung Syetiawan; Dudy Darmawan Wijaya; Irwan Meilano (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Recently, the reflected signals from global navigation satellite systems (GNSS) have been utilized to observe coastal tides, and it has been found that this method provides promising results. Although this method is promising, there remain problems related to accuracy of the observed tides. The purpose of this study was to improve the accuracy by employing an optimal spectral method in the quality control scheme. The quality control process is carried out by setting parameters to achieve the best possible frequency correlated with sea levels such as estimation of the noise frequency range, frequency amplitude power selection, and selection of peak frequency to noise ratio. The results using the data at Morotai station showed that the amplitude power less than 5 comes from low-frequency signals and hence it is an indicator that the Lomb-Scargle periodogram (LSP) fails to determine the dominant frequency. In addition, the result of the peak frequency to noise ratio shows a value of 2.7, meaning that the peak frequency of the LSP signal is at least 2.7 times greater than the signal noise. Quality control sensitivity settings are very effective in determining the reflectors height coming from the sea level. The periodogram visualization can be used to decide which LSP is significant.